Meta-Analysis on Cognitive Benefit of Exercise after Stroke - Bo Yang; Shuming Wang (Complexity)
ObjectiveThe objective of this paper is to evaluate the cognitive benefit of exercise after stroke, so as to provide more accurate and reliable guidance for targeted exercise intervention. Methods. Randomized controlled trials of the relationship between exercise and cognition after stroke were identified in Cochrane Library and PubMed. Methodological quality was assessed using the Cochrane tool of bias. SMD and 95% confidence intervals were calculated, and Chi-squared test (Q) was adopted to estimate the heterogeneity. Results. (a) Twenty-three studies met inclusion criteria, including 1528 participants. Heterogeneity was from low to high such as attention (I2 = 0.00%), executive function (I2 = 0.00%), cognition (I2 = 64%), and working memory (I2 = 77%). (b) The overall effect on cognition was small (SMD = 0.16 [0.04, 0.28]) but significant and there is a difference between cognitive domains in attention (SMD = −0.35 [−0.57, −0.14]), executive function (SMD = −0.24 [−0.40, −0.08]), and working memory (SMD = 0.36 [0.20, 0.53]). (c) Exercise training was less effective before the 18th month after stroke. Higher benefits on cognition were found after combined therapy compared with other exercise programs, and the older the stroke survivors, the less the cognitive benefit of exercise. Conclusion. Small-to-moderate effect of exercise on cognitive benefit after stroke was found, and the effect was moderated by treatment protocols and sample characteristics.